Adaptation in the E-learning systems - Alqahtani, Norah Dhafer (Technium Social Sciences Journal, 2021)
Considering the weakness of traditional e-learning, a multiple of e-learning systems attempt to get individualization into the process of learning by offering learner-centred instruction, the adaptive E-learning system (AES) is seen as one of the more famous models. An AES can tailor its response to different circumstances. This system aims to improve and execute a solution framework for personalized instruction according to a real-time singular difference in education. In other words, AES concentrates on adaptively delivering learning materials. In this survey paper, the AES framework has been discussed with its components, the technologies, and tools employed by this system. Also, this paper discusses some studies that approved the importance of adaption in the e-learning system in the years (2018-2020), and introduced some challenges faced by this system.